2010
DOI: 10.1634/theoncologist.2009-s104
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotectors and Mitigators of Radiation-Induced Normal Tissue Injury

Abstract: The article reviews agents in clinical use or in development as radioprotectors and mitigators of radiation-induced normal tissue injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
330
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(338 citation statements)
references
References 85 publications
(86 reference statements)
4
330
0
4
Order By: Relevance
“…Therefore, the focus has been shifted to the evaluation of the radioprotective potential of plants and herbs (Citrin et al, 2010;Pal et al, 2013), and compounds derived from them. This review attempts to evaluate the roles of fourteen (14) plant extracts or plant-derived compounds in mitigation of radiological effects.…”
Section: Lakhan Kmamentioning
confidence: 99%
“…Therefore, the focus has been shifted to the evaluation of the radioprotective potential of plants and herbs (Citrin et al, 2010;Pal et al, 2013), and compounds derived from them. This review attempts to evaluate the roles of fourteen (14) plant extracts or plant-derived compounds in mitigation of radiological effects.…”
Section: Lakhan Kmamentioning
confidence: 99%
“…[16] Many antioxidants have been shown to limit the toxicity of radiotherapy in animal models. [17] Here, Patil and colleagues investigated the radioprotective effect of two antioxidants, RUT and QRT, in mice.…”
Section: Spotlight On Original Articlesantioxidants Protect Against Dmentioning
confidence: 99%
“…Many hurdles remain, however, and clinical trials with antioxidants have produced mixed results. [17] A remaining challenge is to target the protective effects of antioxidants to normal tissues. The sulfhydryl compound amifostine, which is currently the only radioprotector compound in clinical use, does this quite well already, as it concentrates more rapidly in normal than in tumor cells.…”
Section: Spotlight On Original Articlesantioxidants Protect Against Dmentioning
confidence: 99%
“…Sulfhydryl bond in the structure of l ‐cysteine ( l ‐Cys) allows it to act as a radio protector by scavenging free radicals 22, 23, 24. Experiments in rats demonstrated that animals administered l ‐Cys withstood normally lethal doses of X‐rays25 and showed considerably reduced damage to essential organs compared to untreated animals 26.…”
Section: Introductionmentioning
confidence: 99%